Belief as an Evaluative and Affective Attitude: Some Implications on Religious Belief - Marquez, Leander P. (Social Science Diliman: A Philippine Journal of Society and Change, 2014)
This paper wishes to reconsider how the notion of “belief” is seen in contemporary western philosophy. It is a widely accepted idea today that belief is merely a propositional attitude. However, the article shows that belief is not merely a propositional attitude, but is an evaluative and affective attitude as well. In its treatment of belief, this paper focuses on religious belief, which occupies a central place in the controversy. In particular, the discussion sheds light on the problem of fideism, or the view that religious beliefs cannot be subjected to analysis or evaluation using methods other than its own. Keywords: Belief, attitude, proposition, propositional attitude, evaluative attitude, affective attitude, belief-in, belief-that, fideism